100 tahun pergerakan bahasa dan sastera Melayu, 1888-1988 - Othman Kelantan, S., 1938-; Dewan Bahasa dan Pustaka (Kuala Lumpur : Dewan Bahasa dan Pustaka, Kementerian Pendidikan, Malaysia, 1992)
Development of Malay literature and language, 1888-1988.
In Malay.
Includes bibliographical references and index.
Keywords: Malay literature -- To 1900.; Malay literature -- 20th century; Malay language -- History